Emergency Pharmacist-A Safety Valve In Hospital Emergency (Bangladesh Journal of Medical Science, 2013)
The Emergency Department is a fast-paced work environment. The hectic nature of work in the department often leads to risk of medication error(s). Many factors are involved resulting in wide range of issues. One of the major factors implicated in this regard is verbal orders associated with high risk of dosing errors and therapeutic errors. Pharmacists are experts in the use of medications and bring a unique set of knowledge and skills to the medical team. Active participation of pharmacists in patient care in the hospital emergency department may result in safer and more effective use of medication. These pharmacists are typically involved in assuring appropriate administration of drugs, monitoring patient adherence to therapy, providing drug information to providers, monitoring patient responses and laboratory values, and providing patient education. Since service in the emergency department is getting more and more challenging inclusion of a pharmacist in the team may be an option to improve the situation and help ensure improved care. DOI: http://dx.doi.org/10.3329/bjms.v12i1.13348 Bangladesh Journal of Medical Science Vol. 12 No. 01 January13 pp.10-16